Dates of publication of Bleeker’s Atlas ichthyologique and Poissons de Madagascar - Kottelat, Maurice (Zootaxa, 2013)
The publication dates of the 36 livraisons of Bleeker’s Atlas ichthyologique des Indes orientales néêrlandaises (1862– 1878) are here compiled from reports of the books received by the Royal Academy of Sciences in Amsterdam that were published as supplements to the Verslagen en Mededeelingen der Koninklijke Akademie van Wetenschappen, Afdeeling Natuurkunde. While the dates of livraisons 1–18 were already known with some accuracy, only the publication year was known for livraisons 19–36. The dates are now narrowed to within a month. This source also shows that Poissons de Mad-agascar was published in December 1874 at the latest.